Gray Whales (Eschrichtius robustus) in the Western Chukchi and East Siberian Seas - Miller, R.V.; Johnson, J.H.; Doroshenko, N.V. (ARCTIC, 1985)
During joint Soviet-American shipboard surveys in autumn 1979 and 1980, numerous sightings of gray whales (Eschrichtius robustus) were made in the western Chukchi and East Siberian seas. Gray whales were observed well offshore in ice-free water in 1979, but near the Chukotka coast in 1980. During the 1980 survey, gray whales were observed further west than previously recorded, with three animals seen at 174 08 E longitude, well into the East Siberian Sea. Based on indirect evidence of gray whale behavior and typical prey organisms identified in bottom samples, we assume gray whales are feeding in the western Chukchi Sea during summer and fall. Movement of these animals further west into the East Siberian Sea may occur regularly when ice conditions permit, but it may also be a response to increasing population size over the past several decades, and gray whales may be reoccupying habitat unused during periods of low population caused by commercial whaling.Key words: gray whale, Eschrichtius robustus, cetacean, Chukchi Sea, East Siberian Sea Mots clés: baleine grise de Californie, Eschrichtius robustus, cétacé, mer Tchouktche, mer de Sibérie Orientale